Transforming leadership styles and knowledge sharing in a multicultural context - Paulienė, Rasa (Business, Management and Economics Engineering, 2012)
Despite limitations on comprehensive studies, scholars accept that transformational and transactional leadership theories will have a universal application because these models have capacity for being adapted to different cultural settings. However, more exploration is required in order to develop a strong and consistent picture of the generalizability of culturally-linked leadership styles differently perceived, evaluated or enacted in diverse cultures because the meaning and importance given to the concept of leadership vary across cultures. By comparing and contrasting the number of cultural frameworks of leadership styles and drawing conclusions as to the relationship between leadership styles and culture, more holistic understanding can be attained.